A Statewide Survey of Stakeholders to Assess the Problem Weeds and Weed Management Practices in Nebraska. (2nd July 2018) - Sarangi, Debalin; Jhala, Amit J.
Abstract: Stakeholders were surveyed across Nebraska to identify the problem weeds and assess common weed management practices. A total of 425 responses were returned across four Nebraska extension districts (Northeast, Panhandle, Southeast, and West Central). Collectively, 61.2% of total farmed or scouted areas in Nebraska were under no-till production, and corn and soybean were the major crops (82.3% of total farmed or scouted area). Common waterhemp, horseweed, and kochia were the most problematic weeds statewide. Widespread occurrence of glyphosate-resistant (GR) weeds such as common waterhemp, horseweed, kochia, and Palmer amaranth were a serious problem in GR crop production. Additionally, 60% of growers in Nebraska reported the presence of at least one GR weed species on their farms. The most commonly used preplant burndown herbicides were 2, 4-D and glyphosate, followed by saflufenacil and dicamba. In Nebraska, 74% and 59% of corn and soybean growers, respectively, were using PRE herbicides; however, more than 80% of growers were using POST herbicides for in-crop weed management. Atrazine alone or in premix or tank mix with mesotrione, S -metolachlor, or acetochlor were the most widely applied PRE herbicides in corn and grain sorghum, whereas the most commonly used PRE herbicides in soybean were the inhibitors of acetolactate synthase (ALS) and protoporphyrinogen oxidase (PPO). Glyphosate was the most frequent choice of the survey respondents as a POST herbicide in GR corn and soybean; 2, 4-D was the most commonly used POST herbicide in grain sorghum and wheat. In Nebraska, only 5.2% of total crop area was planted with glufosinate-resistant crops. Most of the respondents (89%) were aware of the new multiple herbicide–resistant crops, and 80% of them listed physical drift and volatility of the auxinic herbicides as their primary concern. Forty-eight percent of survey respondents identified herbicide-resistant weed management as their primary research and extension priority.